Clinical, pathological and endocrinological evaluation of patients with microscopic transsphenoidal pituitary surgery - Ozcelik, Serhat; Gokkaya, Naile; Tiryaki, Mehmet; Aydogdu, Evren; Celik, Mehmet; Yavuzer, Dilek; Aydin Tezcan, Kadriye (Annals of Medical Research, 2021)
Aim: Detailed evaluation of patients in preoperative stage is an important factor that reduces morbidity and mortality as well as the operation itself. In our study, we aimed to examine clinically, pathologically and endocrinologically, the patients who were decided to undergo transsphenoidal surgery, in light of the literature.Materials and Methods: In this retrospective observational study, preoperative and pathological data of consecutive pituitary adenoma patients who applied to our department from January 2019 to June 2020 and underwent transsphenoidal surgery with microscopic methods, were examined.Results: The study included a total of 31 patients. Distribution of patients in relation to pathological diagnoses was as follows: Functional pituitary adenoma (n: 15), non-functional adenoma (n: 11), apoplexy (n: 2), carcinoma metastasis (n: 2) and craniopharyngioma (n: 1). No statistically significant difference was found between functional and non-functional adenomas, in terms of tumor size, cavernous sinus invasion, Ki-67 index and p53 staining pattern (p> 0.05) whereas presence of suprasellar extension and visual field defect were significantly more in non-functional adenomas (p = 0.015, p = 0.045, respectively).Conclusion: Highly invasive character was detected in both functional and non-functional pituitary Ki-67 indexes were low in the study population, increased p53 expression was noticeable. We can state that the Ki-67 index may not be directly proportional to the invasive behavior of the disease.
Keywords: Microscopic; pituitary adenoma; transsphenoidal pituitary surgery